Family function, social support, postpartum depression, and maternal parenting practices: Their impact on infant growth - Ashri Nurfurqoni Fuadah; Hastuti Dwi; Sunarti Euis; Eva Riany Yulina (BIO Web of Conferences)
The postpartum period presents challenges for mothers; requiring adaptation to new roles and family functions while emphasizing the importance of social support. This transition increases the risk of postpartum depression, affecting the mother's ability to care for her baby. During the first year of birth, a baby depends entirely on the mother to grow optimally. This research aimed to analyze the direct and indirect influence of family function, social support, and postpartum depression on infant growth. The study followed a cross-sectional design and involved 130 mothers of six-month-old babies as respondents in Bogor, selected through a random sampling, and was conducted from September to April 2024. The findings revealed that maternal health-nutrition parenting practices affect infant growth (β= 0.320). There was a negative correlation between social support and postpartum depression through family function (β = -0.133). The family function positively affected maternal parenting practices through postpartum depression (β = 0.103) and contributed to infant growth through postpartum depression (β = 0.166). The study emphasizes the significance of enhancing family function to reduce postpartum depression, enhance maternal parenting practices related to nutrition and healthcare, and support optimal infant growth while reducing the risk of stunting.